Impact of broad‐spectrum antibiotic exposures and multidrug‐resistant gram‐negative bacteremia on hematopoietic cell transplantation outcomes. Issue 5 (29th August 2021) - Kaundal, Shaweta; Jandial, Aditya; Singh, Harmandeep; Chopra, Madhu; Kasudhan, Kripa Shanker; Khaire, Niranjan; Khadwal, Alka; Prakash, Gaurav; Jain, Arihant; Suri, Vikas; Patil, Amol; Arora, Amit; et al.
Abstract: Introduction: There is a close association between the use of broad‐spectrum antibiotics, gut microbiome alteration, multidrug resistant (MDR) gram‐negative bacilli (GNB) bacteremia, graft versus host disease (GVHD), and mortality post‐allogeneic hematopoietic cell transplantation (allo‐HCT). This study reports the impact of the high use of carbapenems and colistin and MDR bacteremia pre‐ and post‐HCT on HCT outcomes. Methods: This was a single‐center, partial retrospective, and prospective study from 2016 to 2020. Both pre‐ and post‐HCT antibiotic exposures and blood culture/sensitivity were recorded. MDR GNB was defined as either non‐susceptibility to third‐generation cephalosporin or carbapenems. In the absence of positive cultures, the treating physician escalated antibiotics from third‐generation cephalosporins to carbapenem and/or colistin as per clinical discretion. De‐escalation policy was not strictly enforced. Results: MDR GNB bacteremia was seen in 29 of 76 (38%) of patients peri‐HCT. The utilization rates for carbapenems and colistin was significantly higher in the cohort with MDR GNB bacteremia pre‐HCT (70% vs. 32%, p  = 0.002 and 31% vs. 6.4%, p  = 0.007, respectively) and post‐HCT (100% vs. 74.5%, p  = 0.002, and 55.2% vs. 8.5%, p  < 0.0001, respectively). The cohort with MDR GNB bacteremia had significantly more severe acute GVHD at day+100 (45% vs. 17.5%, p  = 0.009). The median survival was 204 days compared to not reached in the cohort without any MDR GNB bacteremia ( p  = 0.005). Conclusion: This study shows pre‐ and post‐HCT MDR GNB bacteremia is associated with an increased risk of severe acute GVHD and mortality. Patients with MDR GNB bacteremia had higher exposure to pre‐ and post‐HCT carbapenems and colistin.